Phosphoproteomic profiling of feline mammary carcinoma: Insights into tumor grading and potential therapeutic targets - Pruettha Aruvornlop; Sekkarin Ploypetch; Walasinee Sakcamduang; Sirintra Sirivisoot; Tanit Kasantikul; Sittiruk Roytrakul; Narumon Phaonakrop; Nlin Arya (PLoS ONE, 2025)
Feline mammary carcinoma (FMC) is the most prevalent reproductive tumor in queens and is characterized by aggressive metastatic progression and short survival. Protein phosphorylation is a crucial process in cell regulation, with dysregulation linked to cancer progression, including human breast cancer. Although phosphoproteins have emerged as diagnostic and predictive markers in human breast cancer, knowledge remains limited on their role in FMC. In this study, the phosphoproteomic profiles of specimens for FMC grades 1 (n = 6), grade 2 (n = 11), grade 3 (n = 14), and normal controls (n = 6) were compared by phosphoprotein enrichment coupled with liquid chromatography–tandem mass spectrometry. Seventeen downregulated phosphoproteins were identified across all FMC grades, many of which have established roles in human breast cancer pathogenesis and prognosis. Serine/threonine–protein phosphatase was identified as a potential growth promoter and therapeutic target, while acid phosphatase, prostate, and ribonuclease L were identified as tumor suppressors. Furthermore, the ABC-type glutathione-S-conjugate transporter was associated with multidrug resistance. Protein kinase AMP-activated noncatalytic subunit gamma 3 was associated with increased breast cancer risk. In this study, it was also found to be associated with Ki-67 expression in FMC (p = 0.03). These phosphoproteins interacted with various proteins, immune checkpoint molecules, and chemotherapy drugs associated with mammary cancer in both human and feline species. Furthermore, proteins, such as butyrophilin subfamily 1 member A1, keratin, type I cytoskeletal 10, HECT domain E3 ubiquitin protein ligase 3, nuclear receptor binding SET domain protein 3, and stomatin-like 2, were identified and implicated in cancer progression and prognosis. This study is the first phosphoproteomic investigation of FMC, highlighting the interactions of relevant phosphoproteins with other proteins and chemotherapy drugs associated with both feline and human mammary cancers. The findings provide valuable insights for the identification of diagnostic and prognostic biomarkers and potential therapeutic targets in cats with mammary carcinoma.